Inflationsausblick – Kosten des Krieges treiben Inflation in neue Höhen; Inflation outlook: The costs of war drive prices up to new heights - Johannes Mayr (Wirtschaftsdienst, 2022)
– The Russian government's attack on Ukraine and the spiral of sanctions that has been set in motion have heightened inflationary pressure - especially in Europe. The EU's high dependency on Russian oil and gas imports harbours the risk that inflation in Europe will rise significantly and that the economy will suffers from a loss of purchasing power. The pressure on policymakers to take counter-measures is growing. However, the options are limited in the short term and economically very costly. And longer-term consequences must be taken into account. Energy policy and climate policy must be closely linked.
Keywords: E31; E37; 330; Inflation; Energiepolitik; Klimapolitik; Eurozone